Health Village and its place in the Health System - Soheila Kochakyazdi; Amir Asadi; Rahil Ghorbani Nia (Kerman University of Medical Sciences, 2019)
Health Village and its place in the Health System   Kochak Yazdi Soheila1, Asadi Amir2, Ghorbani Nia Rahil3*   1. PhD Student, Health Services Management Research, Center for Hospital Management, Iran University of Medical Sciences, Tehran, Iran. 2.  BSc of Health village of Moheb Company, BSc of Tourism and Architecture Allame Tabatabai University, Tehran, Iran 3. PhD Student in Health Services Management, School of Healthcare Management, Kerman University of Medical Sciences, Kerman, Iran*Correspondence: Kerman University of Medical Sciences, Haft Baghe Alavi Highway, Kerman Tel: 00983431325147                                               Email: r.ghorbani6790@gmail.com Abstract: Background & Objectives: Health Village is a residential/healthcare place for natural remedies combined with other medical treatments. Health village can be set in different sizes, depending on the amount of investments and the investors' strategic objectives. In fact, a complete health village can cover all aspects of health and meet all the health needs of a community. Methods: In this  review study, Persian and English articles  indexed in valid databases such as Google Scholar, SID, Pubmed, Irandoc Science direct and Scopus were searched using the MESH terms of " Health village" and "Health resort" without time limitation. Results: Providing health services in natural areas and away from urban pollution can restore the health and well-being and also can cause psychological and physical relaxation not only in patients but also in those who are interested in living in places with services such as water therapy, herbal therapy, gravel treatments, mud therapy, and other services.  Conclusion: The effort to create environments such as the health village, due to the potential of such centers in providing high levels of physical and psychological comfort for audiences, can be considered as a beneficial local business. Therefore, the health village is an environment that can contribute to the social and economic development while serving the health of the community.   Keywords: Medical Tourism, Health village, Health system   Citation: Kochak Yazdi S, Asadi A, Ghorbani Nia R. Health Village and its place in the Health System. Journal of Health Based Research 2019; 5(1): 57 -71 . [In Persian]